Faktor Risiko yang Berpengaruh Terhadap Status Kontrol Glikemik pada Kehamilan dengan Diabetes Melitus (Studi Kasus Kontrol Pasien di Beberapa RS di Kota Semarang) - Resna Meiwarnis; Ariawan Soejoenoes; Heri Nugroho; Suharyo Hadisaputro; Henry Setyawan (Jurnal Epidemiologi Kesehatan Komunitas, 2016)
Background : The number of diabetes patients was higher in women than men. The high prevalence in women occurs in pregnant women because of the increasing age of childbearing. Commonly, pregnancy in women with diabetes was associated with morbidity and mortality.  Data obtained from Diabetic  Department  King’s  College  Hospital mentioned that  during  pregnancy, a good control of maternal diabetes cause a progressive decline in blood glucose control. The purpose of this research is to explain some risk factors related to glycaemic control status in pregnancy with diabetes mellitus. Methods : This research was an observational study using case control design by using retrospective approach. The population of this study is all cases of pregnancy with diabetes with  the number of sample was 62 people, consist of 31 cases and 31 control with consecutive  sampling. In this research, cases sample selection was chosed from pregnant women with diabetes who come to Tugurejo Hospital, Semarang City Hospital and Roemani Hospital during 2015. Control sample selection was chosed from non pregnant women with diabetes who come to Tugurejo Hospital, Semarang City Hospital and Roemani Hospital during 2015. Results : The pattern of taking medications that was not good (p= 0,002; aOR= 7,2; 95%CI= 1,9-17,2) was risk factors of poor glycaemic control status with probability event amounted was 70,0%. Conclusion : The risk factors to glycaemic control status in pregnancy with diabetes was the pattern of taking medications that was not good. Background  :Thenumber  ofdiabetes  patients  washigher  inwomen  thanmen.Thehigh prevalence   in   women   occurs   in   pregnant   women   because   of   the   increasing   age   of childbearing.  Commonly,  pregnancy  inwomen  withdiabetes  wasassociated  withmorbidity andmortality.  Dataobtained  fromDiabetic  Department  King’s  College  Hospital  mentioned that  during  pregnancy,  agood  control  ofmaternal  diabetes  cause  aprogressive  decline  in bloodglucosecontrol.Thepurposeof thisresearchisto explainsomeriskfactorsrelatedto glycaemiccontrolstatusinpregnancywithdiabetesmellitus.Methods  :Thisresearch  wasanobservational  studyusingcasecontrol  design  by  using  a retrospective  approach.  Thepopulation  ofthisstudyisallcasesofpregnancy  withdiabetes with  the  number  of  sample  was  62  people,  consist  of  31  cases  and  31  control  with consecutive  sampling.  In  this  research,  cases  sample  selection  was  chosed  from  pregnant women   with   diabetes   who   come   to  Tugurejo   Hospital,   Semarang   City   Hospital   and Roemani  Hospital  during  2015.  Control  sample  selection  was  chosed  from  non  pregnant women   with   diabetes   who   come   to  Tugurejo   Hospital,   Semarang   City   Hospital   and RoemaniHospitalduring2015.Results:Thepatternoftakingmedications  thatwasnotgood(p=0,002;aOR=7,2;95% CI=1,9-17,2)was   risk  factors   of  poor  glycaemic   control   status  with  probability   event amountedwas70,0%.Conclusion  :Theriskfactorstoglycaemiccontrolstatusinpregnancywithdiabeteswasthe patternoftakingmedicationsthatwasnotgood.